Translation, cross-cultural adaptation, and measurement properties of the Arabic version of the pain sensitivity questionnaire - Alqarni, Abdullah; Khan, Fayaz; Alabasi, Umar; Ruscheweyh, Ruth (Frontiers in Pain Research, 2024)
Background The Pain Sensitivity Questionnaire (PSQ) is a reliable and valid self-reported tool for the assessment of pain sensitivity in clinical practice. The PSQ has been translated, validated, and cross-culturally adapted into multiple languages. However, a validated Arabic version of the PSQ is not available. Thus, this study aims to translate, validate, and cross-culturally adapt the English version of the PSQ into the Arabic language. Methods and materials The English version of the PSQ was translated and culturally adapted into Arabic following international guidelines. The psychometric properties of the final version of the PSQ-Arabic (PSQ-A) were tested among 119 patients with different persistent musculoskeletal (MSK) pain. Findings The Cronbach’s α for the PSQ-A-total, PSQ-A-moderate, and PSQ-C-minor were 0.81, 0.79, and 0.76, respectively. The means for the PSQ-A-total, PSQ-A-moderate, and PSQ-C-minor scores were 5.07 (±1.28), 5.64 (±2.07), and 4.50 (±0.50). The test-retest reliability measured with the interclass correlation coefficient for 68 subjects was 0.80 for the PSQ-A-total, 0.74 for the PSQ-A-moderate, and 0.77 for the PSQ-A-minor. The PSQ-A-total and the PSQ-A-minor showed positive significant correlations with pain catastrophizing scale (PCS) (r = 0.15, 0.17); P ≤ 0.05), respectively. The PSQ-A-total, PSQ-A-moderate, and PSQ-A-minor showed positive significant correlations with the Brief Pain Inventory (BPI)-pain scores (r = 0.47, 0.43, 0.45; P ≤ 0.01), respectively and with the BPI-pain interference scores (r = 0.37, 0.33, 0.34; P ≤ 0.01), respectively. Conclusions This study shows that the PSQ-A is a reliable and valid tool to assess individuals with pain sensitivity in Arabic populations. Further studies are recommended to examine the concurrent validity of the PSQ-A against experimental pain sensitivity measures.